ملت ابراہیمی کے احیاء کےلیے حضرت عبدالمطلب کی کاوشیں قرآن کی روشنی میں : ایک تحقیقی مطالعہ: Efforts of Hazrat Abd al-Muṭṭalib for the Revival of Millat-e-Ibrāhimī in the Light of the Qur’ān: An Exploratory Study - Rubab Rizvi, Syeda Shumaila; Amjad , Muhammad (Al-Amīr Research Journal for Islamic Studies, 2023)
This exploratory study delves into the remarkable efforts of Hazrat Abd al-Muttalib, the revered grandfather of the Holy Prophet Muhammad, in rejuvenating the Millat-e-Ibrahimi, the Abrahamic faith, in pre-Islamic Arabia. This study investigates the pivotal role played by Hazrat Abd al-Muttalib in preserving and strengthening the monotheistic beliefs of his forefathers, Abraham and Ishmael, against the backdrop of a polytheistic society. Drawing from historical accounts, oral traditions, and early Islamic sources, the research uncovers the strategies and initiatives employed by Hazrat Abd al-Muttalib to foster unity among the disparate Arabian tribes and uphold the principles of monotheism. This study sheds light on a crucial yet often understudied period in Islamic history, exploring the legacy of Hazrat Abd al-Muttalib as a precursor to the prophethood of his grandson, the Holy Prophet Muhammad. By examining his actions and their impact, it provides valuable insights into the early foundations of the Islamic faith and the broader context of religious development in the Arabian Peninsula. Keywords: Hazrat Abd al-Muṭṭalib, Millat-e-Ibrāhimī, Abrahamic faith, Pre-Islamic Arabia, Monotheism, Revival efforts, Arabian tribes۔